Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1677/joe.0.1690299
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone receptor blockade restores cellular immunity in male mice after burn injury

Abstract: Males are known to have increased risk for septic complications after traumatic injury, which appears to be mediated by the inhibitory effects of testosterone on immune function. The role of testosterone in immunity after burn injury, however, remains unclear. Herein, we examined the effects of a testosterone receptor antagonist, flutamide, on delayed type hypersensitivity response (DTH), splenocyte proliferation, interleukin (IL)-2 secretion, and IL-2 receptor (IL-2R) expression in male BALB/c mice subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 44 publications
(56 reference statements)
2
26
0
Order By: Relevance
“…It has long been appreciated that gonadal sex steroids might modulate systemic host immunity (1,9,10,12,24). For instance, autoimmunity has been shown to be more prevalent in women than in men (2-4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been appreciated that gonadal sex steroids might modulate systemic host immunity (1,9,10,12,24). For instance, autoimmunity has been shown to be more prevalent in women than in men (2-4).…”
Section: Discussionmentioning
confidence: 99%
“…Splenocytes derived from Cx compared with Sx mice have also been shown to produce higher levels of IL-2 and IFN-␥ in response to Con A, and increased autoreactive Ab in response to mitogen (12). Additionally, studies have shown that AD may reduce host immunosuppression induced by hemorrhage (1) or burn injury (24). Thus, prompted by these observations, we set out to investigate the impact of AD on Ag/tissue-specific T cell responses in postpubertal Cx compared with Sx mice.…”
Section: Discussionmentioning
confidence: 99%
“…Monocyte-derived macrophages also express androgen receptors (McCrohon et al 2000) and these cells may metabolize testosterone to 5 -dihydrotestosterone (Araneo et al 1991). In this regard, treatment of mice with flutamide, an androgen-receptor blocker, restores previously depressed cellular immunity after brain injury (Messingham et al 2001). However, to the best of our knowledge no study has been reported so far in which the expression of androgen receptors is analyzed in DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Folstad & Karter's (1992) Immunocompetence Hypothesis proposes that secondary sexual features (those resulting from sex hormones) are honest signals of genetic quality because sex hormones, specifically testosterone, are deleterious to the immune system (Angele & Faist, 2000;Messingham, Shirazi, Duffner, Emanuele & Kovacs, 2001). Only high quality, healthy males may be able to tolerate the immunosuppressive effects of testosterone and develop exaggerated secondary sexual traits.…”
Section: Immunocompetencementioning
confidence: 99%